#TITLE_ALTERNATIVE# - HASUDUNGAN SIMANJUNTAK (NIM 13702034), RONALD
Steel slag is a by product from PT. XYZ, a steel melting industry which is a located in Cilegon, Banten. This product contains Silica as a function to improve the interface between aggregate with cement paste and Ferro as a function to add weight of steel slag material. Utilization of steel slag as aggregate on concrete technology could rise air dry unit weight concrete from 2200-2500 kg/m3 to 2800-3000 kg/m3. That change could be fairly significant for heavyweight concrete application. Some of heavyweight concrete applications are weighted concrete on oil and gas pipeline, dam and tetra pod on beach for avoiding seawater abrasions. Increased quality of slag concrete mainly bond strength (contact zone) between cement paste and aggregate could be happen because slag aggregate contains cementious compound in which chemically could react with Calcium Hydroxide compound. This research was carried out to establish the performance of four type aggregate combination of concrete. First combination is concrete type 1 (use natural sand as fine aggregate, stone as coarse aggregate), the second type is concrete type 2 (use slag as fine aggregate, stone as coarse aggregate), the third is concrete type 3 (use natural sand as fine aggregate, slag as coarse aggregate) and the last type is concrete type 4 (use slag as fine and coarse aggregate). For compressive strength concrete type 1 gives optimum result of 37,33 MPa at the age 56, concrete type 2 gives optimum result of 38,1 MPa at the age 56, concrete type 3 gives optimum result of 38,5 MPa at the age 56 and concrete type 4 gives optimum result of 45,43 MPa at the age 56. Scanning Electron Microscopy (SEM) characterization was used to identify aggregate-comatrix interface and XRD characterization was used to predict amount of CSH compound.